2020
DOI: 10.35188/unu-wider/2020/906-8
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural input subsidy and farmers outcomes in Tanzania

Abstract: This paper examines the impact of the government input subsidy—the National Agriculture Input Voucher—on farmers’ production and welfare in Tanzania as well as the factors that influence agricultural production in the country. The analysis is based on the Living Standards Measurement Study-Integrated Surveys on Agriculture for 2008–13. The study uses panel fixed effects and difference-in-difference and propensity score matching methods to examine the two objectives. The results show that the input subsidy prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
(78 reference statements)
0
10
0
Order By: Relevance
“…Since the 1960s, the government introduced 16 National Agriculture Input Voucher Systems (NAIVS) for farmers to access and use modern farm inputs (seeds and fertilizers) through contracted agro-dealers for improved production and income [70]. However, due to lack of government control, cheating and fraud, contracted agro-dealers sell the subsidized inputs at full market price, leading to deficient programs' impact on farmers [71].…”
Section: Digital Technology and Tanzanian Agriculturementioning
confidence: 99%
“…Since the 1960s, the government introduced 16 National Agriculture Input Voucher Systems (NAIVS) for farmers to access and use modern farm inputs (seeds and fertilizers) through contracted agro-dealers for improved production and income [70]. However, due to lack of government control, cheating and fraud, contracted agro-dealers sell the subsidized inputs at full market price, leading to deficient programs' impact on farmers [71].…”
Section: Digital Technology and Tanzanian Agriculturementioning
confidence: 99%
“…A decline in the proportion of MPI poor households followed the same pattern (Figure 3b). Kinuthia (2020) similarly established that rice farmers in Tanzania had improved welfare throughout the interval from 2008 to 2012, which was attributed to the tradable nature of the crop. Comparison by gender showed that farmers in MHH experienced a significantly higher MPI decline (39.3%) as well as the decline in the proportion of MPI poor households (28.1%) compared to FHH, which calls for more efforts to enhance the inclusion of FHH to benefit from rice commercialization.…”
Section: Livelihood Impacts 341 Descriptive Analysismentioning
confidence: 90%
“…But the rate of using inorganic fertilizer (Kg/ha) decreased slightly. Reporting on the impact of the national agricultural subsidy in Tanzania covering eight years (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016), Kinuthia (2020) similarly reported 59% of respondents reduced the use of fertilizer and seed due to high cost and low availability. Meanwhile, there was a significant (p<0.05) increase in the percentage of households as well as the rate (Lt/ha) of using herbicides, reflecting farmers' substituting away from more expensive labour during land clearing and weeding.…”
Section: Changes In Use Of Inputs and Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the rural context, access to land is key to sustainable livelihoods and income increases, particularly for women with restrained access to quality waged work. In Tanzania, most households practise small-scale agriculture with low levels of productivity, highlighting the necessity for effective agricultural policies (see Kinuthia 2020). In this section, we will examine Tanzania's policies aimed at bolstering self-employment, enterprise growth, and agricultural productivity, with their effects on working-age women.…”
Section: Enhancing Skills Among Working-age Women?mentioning
confidence: 99%